Matrix metalloproteinases and small artery remodeling - Martinez-Lemus, Luis A. (2011)
Inward eutrophic remodeling is a common structural change found in small resistance arteries that has been associated with an increased risk for life threatening cardiovascular events, the number one cause of death in industrialized societies. Because inward eutrophic remodeling is the most prevalent small artery structural change found in hypertension, hypertensive animals are the most common in vivo models used to study this particular remodeling process. In vitro, the isolated artery, pressure myograph has also been used as a model to study the mechanisms responsible for the development of small artery remodeling. Compelling recent evidence indicates that the matrix metalloproteinases (MMPs), a family of endopeptidases whose primary function is the cleavage and degradation of extracellular matrix components, are involved in vasoconstriction and the pathogenesis of hypertension. In this review we provide an overview of the known and potential roles that MMPs have on vascular remodeling, paying particular attention to their role on the inward eutrophic remodeling process of small resistance arteries that occurs in hypertension.